A new species of Acrolocha from North Iran (Coleoptera: Staphylinidae: Omaliinae) - Volker Assing (Contributions to Entomology)
A new species of the Holarctic omaliine genus Acrolocha Thomson, 1858 from Gilan province, Northwest Iran, is described, illustrated, and distinguished from other West Palaearctic congeners. The genus now includes a total of 16 species, seven of which are distributed in the West Palaearctic region.